A Banda Corporação Musical Nossa Senhora do Carmo: um espaço de relações e de ensino/aprendizagem musical (1985-2014) - Rezende, Murilo Silva (2016)
This research aims to understand the constitution of the teaching-learning process in music from the social relationships that occur within the brass band, namely Corporação Musical Nossa Senhora do Carmo, from the city of Arcos, MG, during the period of 1985 to 2014. This study intends to understand the social relations and the ways in which they subsidize the teaching-learning process in music; discuss the relations around the teaching /learning process of music which are constituted within the band in terms of sociability; analyze the coexistence within the band and understand how the links established between the members are present in the training of musicians and identify how sociability is constituted through the process of teaching and learning music in that context. It is a qualitative research (DENZIN; LINCOLN, 2006; HESSE-BIBER, 2006) that uses the methodology of Oral History (LEAVY, 2011; MEIHY, 2000) and the collection of data by means of oral sources (interviews), in the written form (newspapers articles), and those which are iconographic (photographs). The theoretical foundations are based upon music education as a social practice (GONÇALVES, 2007; SOUZA, 2004) which does not exist by itself and depends on people and groups that produce, teach and learn music and who mingle for various reasons, constituting forms of sociability in music education (RIEDEL, 1964; GURVITCH, 1941) as the main reason to get together and/or form a band. As a conclusion, the social relations go beyond the scope of the band and make people want to learn music, not necessarily because of the music itself, but due to the sociability that it involves. the teaching-learning impetus of professional musicians, as well as people who are interested in learning music and who wish to play a musical instrument leads such people to be immersed in various pedagogical and musical relationships.